The Effect of Using Red Betel Leaf Decoction on the Healing of Perineal Lacerations in Postpartum Women in the Tunggakjati Community Health Center Area, Karawang Regency, 2025 - Neni Sugiarti; Erina Windiany; Ernawati; Marinem (Journal for Quality in Women's Health, 2026)
Perineal lacerations occur in up to 75% of women undergoing vaginal delivery in Indonesia and may increase the risk of infection if not properly managed. This study aimed to determine the effect of boiled red betel leaf (Piper crocatum) decoction on perineal wound healing in postpartum women. A quasi-experimental study with a two-group posttest-only design was conducted among 37 postpartum women with second-degree perineal lacerations on days 1–6 postpartum at the Tunggakjati Community Health Center, Karawang Regency, in 2025. Participants were assigned to an intervention group receiving red betel leaf decoction a control group using plain water. The intervention group showed a higher proportion of good healing outcomes (94.7%) compared to the control group (61%), with a significant association between treatment and healing (p < 0.05). Boiled red betel leaf decoction is effective as a complementary, non-pharmacological approach for postpartum perineal wound care